Advancement of national interests on the pages of the Ukrainian emigrant press in France during the First liberation struggles of 1917-1921 (on the example of "France et Ukraine" weekly) - Shkabura, Yaroslav (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2024)
The purpose of the article. Based on the analysis of the issues of the French-language periodical "France et Ukraine", published in Paris by Ukrainian emigrants, to find out what place the national interests of Ukraine occupied in the publications and through which plots and theses they tried to promote them.The research methodology. The research used both general scientific methods (structural-systemic), as well as specifically historical (comparative) and interdisciplinary (methods of content analysis, discourse analysis).Scientific novelty. For the first time, the author analyzes a Ukrainian French-language weekly in such detail, introducing all its issues into scientific circulation, examines their content and main emphasis, and the place of national interests in them.The  relevance. The topic of the article is particularly relevant nowadays, as the Russian full-scale invasion of Ukraine caused a wave of forced emigrants to appear in various countries, primarily in Europe. And currently, the issue of interaction with them and the promotion and protection of national interests is an important aspect of Ukraine's foreign policy. Therefore, studying and using previous positive experience is quite logical and necessary.Conclusions. It has been demonstrated that the weekly "France et Ukraine" took a strong pro-Ukrainian position from the very beginning, and on its pages actively promoted pro-Ukrainian narratives, the history of Ukraine, informed the European public about the relevant political and state-building processes, the national liberation movement, tried to strengthen and improve the Ukrainian-French relations.